UNVEILING LINGUISTIC IMPERIALISM IN ELITE EDUCATIONAL INSTITUTIONS: A CASE STUDY - Memoona Samee; Dr. Aftab Akram (International Journal of Contemporary Issues in Social Sciences, 2024)
Within elite educational institutions, this study explored the complex and highly difficult relationships between language imperialism, linguistic identity, and academic success. This case study provided a study of the behaviors that sustained linguistic imperialism within these settings by drawing on qualitative approaches, including teacher and student interviews. The study investigated the perspectives and experiences of multilingual and struggler learners using theme analysis, illuminating their challenges, approaches, and goals. The results highlighted how language rules and teaching methods had a widespread impact on students' cultural identification, academic engagement, and feeling of belonging. By elevating providing insights for academics, policymakers, and educators, the study emphasized the significance of inclusive learning settings and increased knowledge of linguistic imperialism in elite schools. The marginalization of multilingual and linguistic minority students at top educational institutions is exemplified by this example, which highlights the widespread effects of language imperialism. It highlights how crucial it is to have inclusive laws and support networks in order to deal with language variety and advance equal rights.